The Impact of Internal Control Systems on Fraud Prevention in Public Sector Organizations - Davila (Economy, Business, Finance, Accounting & Management Journal, 2025)
Fraud is a common problem in public sector organizations and can result in financial losses to the state, a decline in the quality of public services, and a loss of public trust in government institutions. One measure that can be taken to minimize the risk of fraud is the implementation of an effective internal control system. This study aims to analyze the impact of internal control systems on fraud prevention in public sector organizations. The research method used is a quantitative approach with data collection techniques through the distribution of questionnaires to employees in public sector organizations. The data obtained were analyzed using linear regression analysis to test the relationship between the internal control system and fraud prevention variables. The results show that the internal control system has a positive and significant effect on fraud prevention. The better the implementation of the control environment, risk assessment, control activities, information and communication, and monitoring activities, the higher the level of fraud prevention within the organization. The conclusion of this study affirms that strengthening internal control systems is a critical factor in fostering transparent, accountable, and fraud-free governance in public sector organizations